Syntheses, structures, and magnetic properties of three two-dimensional cobalt(ii) single-ion magnets with a CoIIN4X2 octahedral geometry. Issue 20 (3rd May 2019) - Shi, Le; Shen, Fu-Xing; Shao, Dong; Zhang, Yi-Quan; Wang, Xin-Yi
Abstract : Three two-dimensional Co II SIMs with (4, 4) layer structures have been synthesized and characterized structurally and magnetically. Abstract : Three two-dimensional Co II complexes, namely, [Co(dps)2 Cl2 ] n (1 ), [Co(dps)2 Br2 ] n (2 ), and [Co(dps)2 (H2 O)2 ·I2 ·(H2 O)4 ] n (3 ) (where dps = 4, 4′-dipyridyl sulfide), have been synthesized using a rationally designed synthetic approach and characterized structurally and magnetically. Although they crystallize in different space groups, these compounds all have similar two-dimensional (4, 4) layer structures where the Co 2+ centers are bridged by the bis(monodentate) ligand dps. In addition, the coordination geometry of the Co 2+ centers is of a general CoN4 X2 octahedral environment formed by four equatorial N atoms from four dps ligands and two X atoms (X = Cl, Br, and O atoms for1–3, respectively) in the axial positions. Ab initio calculations revealed that due to the strong spin–orbit coupling, the spin Hamiltonian containing the zero-field splitting parameters D and E cannot be used to describe their magnetic anisotropy. According to the calculation, the g z values for the spin–orbit ground doublets of1–3 are larger than the g x and g y values, which indicates the easy-axis magnetic anisotropy of these compounds. Due to the existence of the magnetic anisotropy, field-induced single-ion magnet behavior can be observed in all these complexes. This work illustrated that care should be taken to interpret the magnetic data of octahedral Co II compounds. In addition, extended frameworks with long and flexible organic spacers are good candidates for the construction of SIMs with different axial ligands and different magnetic properties.